GAMBARAN PENGETAHUAN DAN SIKAP PASIEN TUBERKULOSIS PARU TERHADAP PENYAKIT TUBERKULOSIS PARU DI PUSKESMAS HARAPAN RAYA KOTA PEKANBARU PERIODE JUNI-DESEMBER 2014 - Syafefi, Charla; ", Suyanto; Endriani, Rita (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
Tuberculosis is infectious disease caused by Mycobacterium tuberculosis. Good knowledge and attitude of patient with tuberculosis about the disease will help to eradicate and prevent pulmonary tuberculosis disease. The purpose from this study was to determine knowledge and attitude pulmonary tuberculosis patient about pulmonary tuberculosis disease. The study was a descriptive crossectional. This study conducted in December 2014 till January 2015. The sampel in this study were 30 pulmonary tuberculosis patients which inclusion criteria. The instrumen used was questionnare. The patient age majority were in the range 25-34 years old as many as 10 people (33,3%), sex characteristic of patient were predominantly male as many as 16 people (53,3%), the patient education is largely completed senior high school as many as 11 people (36,6%) and mainly patient are unoccupied or housewife as many as 11 people (36,6%). The result shows that the respondent who has a moderate level of knowledge as many as 19 people (63,3%) and a good level of attitude as many as 17 people (56,7%).Keywords: Knowledge, attitude, pulmonary tuberculosis